A quantifiable cloud computing platform security evaluation model - Jian XU; Li JIN (Dianxin kexue)
A quantifiable security assessment model for accessing different clouds based on a consistent API was proposed.The evaluation system includes a security scan engine module,a security recovery engine module,a security quantitative evaluation module,and a visual display module.The progress of safety assessment and remediation was proposed,and simulation verification was carried out based on the G-Cloud platform.The results show that the proposed model can display the dynamic security scan scores of one or more clouds through visual graphics,which can guide electricity users to modify configurations,improve operations,repair vulnerabilities,and improve the security of cloud electricity resources.